Melatonin modulates daily and seasonal rhythmic secretary pattern of endocrinological profiles in mithun bull - PERUMAL, P; DE, A K; VIKRAM, R; KHAN, M H; NAHAK, A K; MISHRA, P C (The Indian Journal of Animal Sciences, 2021)
Present study was designed to evaluate the effect of slow release exogenous melatonin on endocrinological profiles in 24:00 hours in adult mithun bulls during different seasons (winter, spring, summer and autumn). Mithun bulls (n=12) were selected and divided into two groups, Gr I: Control (n=6) and Gr II: Treatment (n=6; melatonin implant @ 18 mg/50 kg bwt). Endocrinological profiles such as follicle stimulating hormone (FSH), luteinizing hormone (LH), testosterone, cortisol, thyroxine (T4), insulin like growth factor-1 (IGF-1), prolactin and melatonin (MT) were estimated at 04:00 h interval (08:00, 12:00, 16:00, 20:00, 24:00 and 04:00 h) for one whole day in four seasons. Melatonin treated group had significantly higher FSH, LH, testosterone, IGF-1 and MT than control group; and MT significantly reduced the level of T4, cortisol and prolactin in different seasons at different collection times. The study concludes that MT has significantly improved the endocrine profiles in different seasons and collection times. MT treatment and spring and winter season had significantly greater beneficial effects on reproduction and artificial breeding programs in mithun species in the semi-intensive management in the present location.